2004
DOI: 10.1016/j.bbrc.2004.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine is a key regulator for amino acid-controlled cell growth through the mTOR signaling pathway in rat intestinal epithelial cells

Abstract: Amino acids, especially branched-chain amino acids such as l-leucine, have been shown to regulate activation of p70 S6 kinase and phosphorylation of 4E-BP1 through the mTOR signaling pathway. In our recent study, l-arginine was also shown to activate the mTOR signaling pathway in rat intestinal epithelial cells. l-Glutamine is an amino acid that is required for culturing of numerous cell types, including rat intestinal epithelial cells. In this study, we showed that l-glutamine inhibited the activation of p70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 31 publications
4
59
2
Order By: Relevance
“…Numerous other studies have confirmed the role of leucine in activating the mTOR signaling pathway in certain cells including the intestine [37][38][39]. In the presence of leucine or other recently identified amino acids such as arginine, p70 S6 kinase and eIF-4E binding protein 1 are activated by mTOR.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous other studies have confirmed the role of leucine in activating the mTOR signaling pathway in certain cells including the intestine [37][38][39]. In the presence of leucine or other recently identified amino acids such as arginine, p70 S6 kinase and eIF-4E binding protein 1 are activated by mTOR.…”
Section: Discussionmentioning
confidence: 87%
“…These results indicate that mTORC1 pathway activation in the Apc ⌬716 intestinal polyps is independent of Erk and AMPK signaling. Nutrients such as leucine can also activate the mTORC1 pathway (21). Starved WT mice showed reduction in the S6 phosphorylation level in the normal intestinal epithelium compared with free-feeding WT mice.…”
Section: Inhibitory Effect Of Rad001 On Polyp Formation Is Attributabmentioning
confidence: 99%
“…Previous studies have reported that glutamine can inhibit mTORC1 activity in vitro using cultured cells deprived of serum and amino acids, a nonphysiological condition (Nakajo et al 2005;Deldicque et al 2008). We questioned if glutamine infused into the rat hippocampus can have similar effect in vivo, as assessed by phosphorylation of the known downstream targets ribosomal S6 kinase (S6K) and ribosomal protein S6 (S6).…”
Section: Glutamine Inhibits Mtorc1 Activity In Vivomentioning
confidence: 98%
“…However, other studies have demonstrated that glutamine can either inhibit (Nakajo et al 2005;Deldicque et al 2008) or stimulate (Nicklin et al 2009;Chiu et al 2012;Willems et al 2013) mTORC1 activity, although the mechanism(s) through which this is accomplished are not yet clear. Although these and other studies that have examined the influence of glutamine on mTORC1 activity using cells cultured in vitro, they were typically carried out using serum-and/or amino acid-free conditions to induce a state of starvation.…”
mentioning
confidence: 99%